2016
DOI: 10.1097/md.0000000000002328
|View full text |Cite
|
Sign up to set email alerts
|

High Stroke Volume Variation Method by Mannitol Administration Can Decrease Blood Loss During Donor Hepatectomy

Abstract: Optimal fluid management to reduce blood loss during donor hepatectomy is important for maximizing donor safety. Mannitol can induce osmotic diuresis, helping prevent increased intravascular volume status. We therefore evaluated the effect of high stroke volume variation (SVV) method by mannitol administration and fluid restriction on blood loss during donor hepatectomy.In this prospective study, 64 donors scheduled for donor right hepatectomy were included and allocated into 2 groups. In group A, the SVV valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
10
1
1
Order By: Relevance
“… 10 , 22 , 23 Importantly, our group has previously suggested that maintaining a high SVV is a useful way to reduce blood loss during living donor right hepatectomy. 10 , 11 , 24 Additionally, a higher SVV value has been reported to correlate with a lower right ventricular end-diastolic volume index value in liver transplant recipients. 12 The maintenance of a high SVV appears to induce lower normal levels of intravascular volume and to thereby prevent vascular congestion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 10 , 22 , 23 Importantly, our group has previously suggested that maintaining a high SVV is a useful way to reduce blood loss during living donor right hepatectomy. 10 , 11 , 24 Additionally, a higher SVV value has been reported to correlate with a lower right ventricular end-diastolic volume index value in liver transplant recipients. 12 The maintenance of a high SVV appears to induce lower normal levels of intravascular volume and to thereby prevent vascular congestion.…”
Section: Discussionmentioning
confidence: 96%
“… 8 , 9 Recently, our group found that blood loss during living donor hepatectomy was significantly lower in donors who maintained 10-20% of stroke volume variation (SVV) compared with those who maintained <10% of SVV. 10 , 11 However, no study has yet reported the relationship between the high SVV method (i.e. maintaining 10-20% of SVV during surgery) and intraoperative blood transfusion in liver transplant recipients, who are frequently at risk for blood transfusion during liver transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…1). During the period of this study, 2 reports were presented regarding high SVV management during liver transection in livingdonor right hepatectomy set at 10%-20%, 19,20 but there has been no report of management with SVV as an indicator in conventional open-liver resection for liver diseases. In this study, to achieve the target SVV, we mainly addressed fluid restriction only.…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al, however, reported that administration of mannitol at 0.5 g/kg was effective in high SVV management. 20 Furthermore, some reports show that reverse Trendelenburg position leads to a reduction in CVP, 21 and that low CVP is maintained by vasodilation using isoflurane and sublingual nitroglycerine. 22 It is highly possible that these results will be applied to intraoperative management with SVV in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Pada penelitian yang telah dilakukan sebelumnya, ditunjukkan bahwa manitol secara aman dan efektif dapat mempertahankan variasi volume strok tinggi sebesar 10-20% untuk mengurangi kehilangan darah selama donor hepatektomi hidup. 16 Selanjutnya, persentase penggunaan cairan asering lebih rendah dibandingkan dengan yang lainnya disebabkan asetat dalam larutan asering lebih banyak dimetabolisme dalam otot dan sebagian kecil dalam ginjal Volume 7, Nomor 4, Desember 2018 dan jantung, dalam hal ini pada pasien strok cenderung mengalami atrofi otot berbeda dengan laktat yang dimetabolisme di dalam hati. Selain itu, asering dapat berinteraksi dengan obat lain yang digunakan pada pasien strok seperti aspirin pada dosis 80-100 mg digunakan sebagai antikoagulan pada pasien strok.…”
Section: Pembahasanunclassified